Editorial Commentary: Hip-Spine Syndrome: When the Hip Does Not Move, the Spine Labors Double (2021)
When the hip does not move, the spine labors double. For example, limited hip extension results in lumbar spine hyperextension and an increase in spinal facet joint loading due to premature coupling. Patients who undergo hip surgery show significant improvement in concomitant lower back problems, and symptomatic low back pain resolves in approximately 80% of patients after total hip arthroplasty. When an impairment in hip range of motion (limitation or asymmetry) is identified, a logical relationship to lumbar pathology should be explored, and treatment options may include interventions that improve hip joint range of motion.